2012
DOI: 10.1021/es3025325
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Transfer of Au Nanoparticles from Soil along a Simulated Terrestrial Food Chain.

Abstract: To determine if nanoparticles (NPs) could be transferred from soil media to invertebrates and then to secondary consumers, we examined the trophic transfer of Au NPs along a simulated terrestrial food chain. Earthworms (Eisenia fetida) were exposed to Au NPs in artificial soil media and fed to juvenile bullfrogs (Rana catesbeina). Earthworm Au concentrations were continuously monitored so that the cumulative dose to bullfrogs could be accurately estimated throughout the experiment. We exposed a second group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 32 publications
8
93
2
Order By: Relevance
“…Bioaccumulation efficiency (bioaccumulation factor ¼ 0.16) was much lower for dietary consumption of surface-contaminated plant material than for consumption of plant material within which MNMs had been accumulated via root uptake. Similarly, Unrine et al (2012) investigated trophic transfer of tannic acid Au MNMs from earthworms to bullfrogs and compared transfer efficiency of this pathway with direct gut gavage exposure in the presence of control worms. As was the case with the hornworms, bioaccumulation efficiency in the bullfrogs was higher via ingestion of the earthworms than by gut gavage.…”
Section: Dietary Uptake and Trophic Transfer Of Nanoparticles In Terrmentioning
confidence: 99%
“…Bioaccumulation efficiency (bioaccumulation factor ¼ 0.16) was much lower for dietary consumption of surface-contaminated plant material than for consumption of plant material within which MNMs had been accumulated via root uptake. Similarly, Unrine et al (2012) investigated trophic transfer of tannic acid Au MNMs from earthworms to bullfrogs and compared transfer efficiency of this pathway with direct gut gavage exposure in the presence of control worms. As was the case with the hornworms, bioaccumulation efficiency in the bullfrogs was higher via ingestion of the earthworms than by gut gavage.…”
Section: Dietary Uptake and Trophic Transfer Of Nanoparticles In Terrmentioning
confidence: 99%
“…[60][61][62][63] However, several NPs with conflicting results have been reported to have no biomagnification effects in food chains. [64][65][66][67] Tangaa et al 68 and Unrine et al 69 suggested that the discrepancies among BMFs could be due to both abiotic (eg, environmental parameters) and biotic (eg, organism physiology and life-history traits, foodweb structure, and analyses of whole-body vs single-organ concentration) that affect the efficiency of trophic transfer.…”
mentioning
confidence: 99%
“…GNP transfer in the terrestrial trophic chain from tobacco (Nicotiana Tabacum L. cv Xanthi) to the tobacco hornworm Manduca sexta was studied and biomagnification was noted [48]. Likewise, GNP transfer and accumulation in the terrestrial trophic chain from the earthworm Eisenia fetida to the bullfrog Rana catesbeina was also studied and noted similar results of biomagnification along with accumulation in liver, kidney, spleen, muscle, stomach and intestines [49].…”
Section: Environmental Fate Of Gnpsmentioning
confidence: 94%